Which attitudes preservice teachers' have towards environmental ethics - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
The purpose of this study is to find which approaches preservice teachers' have regarding environmental ethics. Preservice teachers from different teacher education programmes (science education, pre-school education, primary school education, social sciences education) in Department of Elementary Education in two universities were participated for this study. All of the participants were seniors who were ready to be teachers in elementary schools. A questionnaire about environmental ethics was completed by them. Responses of the questionnaire were analysed by using statistical methods. It was found that while no difference were found in levels of ecocentic approach statistically, in levels of apathy approach significant differences were found between teacher education programmes, and also it was found that preservice teachers participated an environmental course have higher level of ecocentric concern. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: Environmental ethics; preservice teachers; teacher education programmes; GENDER